The Mediating Role of Risk Management in the Relationship Between Financial Technology Adoption and Business Growth in Indonesian MSMEs - Judijanto, Loso; Dewi, Yuli; Dewi, Arlinta Prasetian; Barus, Imelda; Firdaus, Adhy (West Science Journal Economic and Entrepreneurship, 2025)
This study examines the mediating role of risk management in the relationship between financial technology (fintech) adoption and business growth in Indonesian Micro, Small, and Medium Enterprises (MSMEs). A quantitative approach was employed with a sample of 125 MSMEs, utilizing a 5-point Likert scale for survey data and Structural Equation Modeling (SEM) with Partial Least Squares (PLS) for analysis. The results indicate a significant positive relationship between fintech adoption and risk management, as well as between risk management and business growth. Moreover, fintech adoption positively impacts business growth both directly and indirectly through the mediating effect of risk management. The findings highlight the importance of integrating fintech solutions with robust risk management frameworks to foster sustainable growth in MSMEs. Policy implications suggest that MSME owners, fintech providers, and policymakers should focus on enhancing risk management practices to maximize the benefits of fintech adoption.